2020
DOI: 10.1007/s42398-020-00125-x
|View full text |Cite
|
Sign up to set email alerts
|

The nexus between meteorological parameters and COVID-19 pandemic: case of Islamabad, Pakistan

Abstract: The study aimed to investigate the correlation between meteorological parameters and the spread of the COVID-19 pandemic in Islamabad, Pakistan. The meteorological parameters include temperature minimum (°C), temperature maximum (°C), temperature average (°C), humidity minimum (%), humidity maximum (%), humidity average (%), and rainfall (mm). The data of COVID-19, such as the number of new confirmed cases and deaths was obtained from the Ministry of Health, Pakistan. The correlations of various types, i.e., P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
3
4
0
Order By: Relevance
“…Alternatively, the result is consistent to the findings by Babu et al (2020) which do not report any significant correlation between temperature, humidity, and COVID-19 cases in Delhi, India. Similar case is also evident in the study by Rehman et al (2020), where the authors opine no relationship of higher temperature and humidity with COVID-19 proliferation in Islamabad, Pakistan. In the case of Sri Lanka, humidity and wind speed exhibit the most noteworthy impact on the confirmed cases (at 5% and 1% significant level), which is also evident from the results proven by Jayadevan et al (2021) where 87% humidity in Colombo resulted in a surge in infections across the city.…”
Section: Resultssupporting
confidence: 74%
“…Alternatively, the result is consistent to the findings by Babu et al (2020) which do not report any significant correlation between temperature, humidity, and COVID-19 cases in Delhi, India. Similar case is also evident in the study by Rehman et al (2020), where the authors opine no relationship of higher temperature and humidity with COVID-19 proliferation in Islamabad, Pakistan. In the case of Sri Lanka, humidity and wind speed exhibit the most noteworthy impact on the confirmed cases (at 5% and 1% significant level), which is also evident from the results proven by Jayadevan et al (2021) where 87% humidity in Colombo resulted in a surge in infections across the city.…”
Section: Resultssupporting
confidence: 74%
“…The influence of season and climate parameters, precisely atmospheric temperature, and humidity, on many viruses, were mentioned in several previous studies [2,3,34,35]. Similar to the above, many studies showed an inverse association between air temperature and COVID-19 spreading [36][37][38][39][40], with a significant correlation between recovery time and solar radiation exposure [41]. Solar radiation, specifically UV radiation, has the ability to inactivate the virus and boost the immune system through vitamin-D preparation and thereby slow the infection rate [42][43][44][45]…”
Section: Resultssupporting
confidence: 57%
“…Most recent studies related to the emission of pollutants during the COVID-19 pandemic have evaluated changes in air quality compared with a period prior to the lockdown (Aydin et al 2020 ; Bashir et al 2020 ; Collivignarelli et al 2020 ; Dantas et al 2020 ; Mahato et al 2020 ; Muhammad et al 2020 ; Nakada and Urban 2020 ; Otmani et al 2020 ; Rodríguez-Urrego and Rodríguez-Urrego 2020 ; Sarkar et al 2020 ; Sicard et al 2020 ). Some authors sought to correlate other aspects, such as climatic variables and the spread or lethality of COVID-19 (Conticini et al 2020 ; Fattorini and Regoli 2020 ; Guo et al 2020 ; Hendryx and Luo 2020 ; Jahangiri et al 2020 ; Kerimray et al 2020 ; Ogen 2020 ; Prata et al 2020 ; Rehman et al 2020 ; Singh et al 2020 ; Qi et al 2020 ). The effect of mobility habits in the spread of the Coronavirus in Italy was analyzed by Cartenì et al ( 2020 ) in Italy, while Bao and Zhang ( 2020 ) related mobility indices to air quality in the lockdown period in Chinese cities.…”
Section: Introductionmentioning
confidence: 99%